A study for obtaining more compacton solutions of the modified form of fifth-order Korteweg-de Vries-like equations - İnç, Mustafa (Verlag Z Naturforsch, 2004)
In this paper we investigate exact solutions of a modified form of fifth-order Korteweg-de Vries-like equations by using two direct methods. Thus we get new compacton solutions having infinite wings or tails. In addition, new periodic and singular periodic wave solutions are obtained.
Keywords: modified form of fifth-order KdV-like equations; compacton; periodic wave solution